Examining the utility of the Stages of Change model for working with offenders with learning disabilities. Issue 2 (11th June 2018) - Panting, Holly; Swift, Charlotte; Goodman, Wendy; Davis, Cara
Abstract : Purpose: The purpose of this paper is to investigate whether the Stages of Change (SOC) model can be applied to working with offenders with learning disabilities (LD), and furthermore, to determine if it might be efficacious for this approach to be incorporated into a wider service model for this population. Design/methodology/approach: This paper reports on the results of a consultation to a specialist forensic LD service in the South West of England. A two-pronged approach was taken to consult to the service in relation to the research questions. First, a comprehensive literature review was undertaken, and second, other forensic LD teams and experts in the field were consulted. Findings: There is a dearth of research that has examined the application of the SOC model to working with offenders with LD, and as such, firm conclusions cannot be drawn as to its efficacy in this population. The evidence base for the SOC model in itself is lacking, and has been widely critiqued. However, there are currently no other evidence-based models for understanding motivation to change in offenders with LD. Research limitations/implications: There is a clear clinical need for more robust theory and research around motivation to change, which can then be applied to clinical work with offenders with LD. Originality/value: There has been a historical narrative in offender rehabilitation that "nothing works" (Burrowes and Needs, 2009). As such, it is more important than ever for the evidence base to enhance the understanding of motivation to change in offending populations.